Hukum Kepailitan dalam Eksekusi Harta Benda Korporasi sebagai Pembayaran Uang Pengganti - Sidabutar, Lambok Marisi Jakobus (Komisi Pemberantasan Korupsi, 2019)
There are issues faced by the Prosecutor’s Offices in executing corporate assets as compensation payment at the time the assets are used as collateral for debt to creditors. In this condition, the execution of corporate assets as payment of replacement money through criminal channels cannot play an optimal role. This article focuses on knowing the obstacles faced by the Prosecutor's Office in executing money instead of corruption cases. Also, to find out the use of bankruptcy law as a legal instrument in executing corporate assets as a form of payment for replacement money. The use of bankruptcy law as the instrument in executing corporate assets has fulfilled the requirements for bankruptcy as regulated in Article 2 Paragraph (1) Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations. The Prosecutor’s Office must be able to prevent arrears in payment of compensation by recording and confiscating the corporate assets that must be carried out since the investigation.